Limnological comparison of two peridunar ponds in the Doñana National Park (Spain) - López, Teresa (1991)
The ponds Santa Olalla and Dulce belong to the peridune pond system on the E—W coastline of the Doñana National Park. The water that fills these ponds originates in the groundwater tables of the dunar system, and these ponds also contain rainwater (run-off and drainage). Despite the fact that they are contiguous ponds,which join up during determined periods, they present differences, both in water chemical characteristics and in their phyto- and zooplanktonic communities. Santa Olalla shows conductivity values of 3 to lOmS/cm in the dry period, and of 0.5 to 3mS/cm in the rainy one. Its water is sodium chloride enriched. The pH values vary between 7 and 11. It is a hypereutrophic pond with chlorophyll-a at higher concentration than 100mg/m3 in most of the samples. The phytoplankton community is dominated by Spindina platensis, Anabacnopsis circtdaris, Microcystis aeruginosa, Apha- nothece clathrata and Coelospbaerium kuetzingianum. The zooplankton is dominated by Bracbionus plicatilis, Keratella quadrata, Daphnia magna and Acantbocyclops robustus. Dulce presents a lower salinity (conductivity values between 0.8 and 2.5mS/cm in the dry period and between 0.25 and 1.7 in the rainy one) and althouhg it also has sodic chloride enriched water, the proportion of divalent cations is higher than Santa Olalla. The pH values vary between 6 and 9.5. Macrophyte develop in this pond. The phytoplankton community is dominated by Chroococcus dispersas, Merismopoedia punctata, Aphanocapsa elaebista, Kirchneriella microscópica, Monorapbidium spp and Scenedesmus spp. The zooplankton is dominated by Acantbocyclops robustus and Arctodiaptomus wierzejski.